2021
DOI: 10.1111/tgis.12720
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on the use, processing and fusion of geographic data in virtual assistants

Abstract: Virtual assistants are a growing area of research in academia and industry, with an impact on people’s daily lives. Many disciplines in science are moving towards the incorporation of intelligent virtual assistants in multiple scenarios and application domains, and GIScience is not external to this trend since they may be connected to intelligent spatial decision support systems. This article presents a scoping review to indicate relevant literature pertinent to intelligent virtual assistants and their usage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Compared with QA, GeoQA is a smaller research topic which starts attracting attentions from QA researchers as well as GIScientists only recently. A recent review on the usage of geospatial information in virtual assistants (Granell et al, 2021) also showed that the usage of different types of geographic data and various spatial methods in virtual assistants is quite limited. How we can show the unique contribution of GeoQA to the general QA community is the golden question needed to be answered for GIScientists.…”
Section: Discussion About the Question Classificationmentioning
confidence: 99%
“…Compared with QA, GeoQA is a smaller research topic which starts attracting attentions from QA researchers as well as GIScientists only recently. A recent review on the usage of geospatial information in virtual assistants (Granell et al, 2021) also showed that the usage of different types of geographic data and various spatial methods in virtual assistants is quite limited. How we can show the unique contribution of GeoQA to the general QA community is the golden question needed to be answered for GIScientists.…”
Section: Discussion About the Question Classificationmentioning
confidence: 99%
“…Compared with QA, GeoQA is a smaller research topic which starts attracting attentions from QA researchers as well as GIScientists only recently. A recent review on the usage of geospatial information in virtual assistants (Granell et al, 2021) also showed that the usage of different types of geographic data and various spatial methods in virtual assistants is quite limited. How we can show the unique contribution of GeoQA to the general QA com-14 http://nlpprogress.com/english/question_answering.html munity is the golden question needed to be answered for GIScientists.…”
Section: Discussion About the Question Classificationmentioning
confidence: 99%
“…While there have been advancements in artificial intelligence and geospatial analysis, there is still a need for topographical field data collection by professional surveyors, indicating technological limitations (Levin et al, 2020). Additionally, the study by highlights gaps and limitations in the use of spatial methods, standards, and resources available in spatial data infrastructures to develop intelligent decision systems based on virtual assistants for various application domains, emphasizing the existing technological barriers (Granell et al, 2021). Ethical and legal implications also present challenges in the application of geospatial intelligence for urban security enhancement.…”
Section: Challenges and Limitationsmentioning
confidence: 95%
“…GeoAI leverages recent breakthroughs in machine learning and advanced computing to achieve scalable processing and intelligent analysis of geospatial big data (Li, 2020). This has significant implications for urban security, as it enables the development of intelligent decision systems based on virtual assistants, contributing to the psychological security of urban residents (Granell et al, 2021;.…”
Section: Future Outlookmentioning
confidence: 99%